Late presentation of windsock type congenital duodenal stenosis after mushroom impaction - Mitsumasa Okamoto (Elsevier, 2022)
Late-onset congenital duodenal stenosis is often diagnosed by computed tomography (CT) or upper gastrointestinal series (UGIS). However, there is a high risk of aspiration when performing UGIS with a large amount of gastric residue and we want to avoid unnecessary radiation exposure as much as possible in infants. We performed ultrasonography (US) and impaction of mushrooms into the stenotic portion at the duodenal descending portion was found clearly. Two impacted shimeji mushrooms were successfully removed by an upper gastrointestinal endoscopic procedure. In the procedure, the stenotic portion looked like a pin hole, and the papilla of Vater could not be seen. After the endoscopic procedure, a laparotomy was performed and the membrane was identified and resected; the membrane was in the form of a “windsock”. Ultrasonographic diagnosis and surgical membrane resection by laparotomy are safe and effective procedures for the management of late-onset congenital duodenal stenosis in children.